Comparison of infliximab versus ciclosporin during the initial 6-month treatment period in Behçet disease. Issue 3 (18th August 2009) - Yamada, Yukiko; Sugita, Sunao; Tanaka, Hiroyuki; Kamoi, Koju; Kawaguchi, Tatsushi; Mochizuki, Manabu
Abstract : Aim: To compare the efficacy and safety of infliximab versus ciclosporin A (CsA) in refractory uveoretinitis in Behçet disease. Methods: In this retrospective clinical chart review of patients with Behçet disease who were treated with CsA or infliximab, we collected information on the number of uveitis attacks, visual acuity and adverse side effects that occurred during the 6 months prior to and after the initiation of CsA (n=20) or infliximab (n=17). Results: The number of acute episodes of uveitis during the 6 months before and after initiation of CsA were 3.3±2.4 and 1.2±1.2, and those of infliximab were 3.1±2.7 and 0.4±1.0, respectively (p<0.005). The number of episodes after infliximab administration was significantly lower than that seen for CsA (p<0.05). During the 6-month treatment period, there were no significant differences noted in the improvement of the visual acuity between the two therapies. After CsA administration, neurological symptoms and renal toxicity were seen in one patient each, while after the infliximab administration, an infusion reaction and leucopenia were seen in one patient each. Conclusion: During the initial 6 months of treatment, infliximab proved to be more effective in reducing acute episodes of uveitis in Behçet disease.